HOW FARMERS ADAPT TO CLIMATE CHANGE IN AGRICULTURAL PRODUCTION: A CASE STUDY IN KY SON COMMUNE, KY ANH DISTRICT, HA TINH PROVINCE - Quang Thoai, Trinh (Journal of Forestry Science and Technology, 2022)
Agriculture has become an extremely vulnerable industry to the impacts of climate variability and change. Thus, strengthening adaptation capacity to climate change in agriculture is a societal priority in most of countries in the world, especially in the developing countries where a large number of people depended on agricultural production. The results of the study show that climate change signals have been really clear in Ky Son commune through increasing extreme weather events, especially drought and hot spell. Farmers in Ky Son commune have revealed a lot of risks caused by climate change for their agricultural production. Farmers in the commune have considered adaptive strategies to climate change in agricultural production, of which weather forecasts update and changing crop varieties are the most popular adaptive strategies. The study indicated 7 factors that have significant effects on farmers’ decision in adaptation to climate change in agricultural production in the Ky Son commune, of which attendance in the training courses is the factor that have highest effect level. The study proposed the policies to improve farmers’ adaptive capacity to climate change in agricultural production in Ky Son commune including: (1) Broadening training courses on climate change; (2) Continuing the preferential credit; (3) Promoting large-scale production patterns; and (4) Downscaling and Localizing weather forecast information.